Physical and Mechanical Properties of Coffee Cherries and Beans in Africa: Review and the State of Arts - AHOUANSOU, ROGER H.; SEMASSOU, GUY CLARENCE (My University, 2022)
Coffee is an important source of income for African smallholder farmers. The world is predominated by three coffee varieties, namely Arabica, Robusta, and Liberica originated in the African countries. However, the low coffee quality attributes can affect the coffee beans‟ price due to the improper post-harvesting processes. Therefore, this work is aimed to review the physical and mechanical properties of the African coffee cherries and beans on the country-wise level, and review the methods used to measure quality parameters and compare the key coffee quality parameters. This work was qualitatively conducted using secondary data on African Arabica and Robusta coffee from journals, conference proceedings, and reports. Methods used for determining the coffee beans‟ properties were explored country wise. The coffee attributes of the two coffee varieties were compared through statistical analysis using ANOVA. The review found that the coffee quality depends on geographical characteristics, agronomic factors, and post-harvesting processes. The coffee cherries de-pulping process is linked to the coffee quality to avoid the damage of parchment coffee beans based particularly on the size and shape of coffee cherries and beans. The analysed quality parameters showed that the Ethiopian Arabica coffee beans were larger than the Ghanaian Robusta coffee beans. While the size of Robusta coffee in Eastern African countries, particularly Uganda, is bigger than those in Western countries, especially Ghana. Therefore, the information on the coffee quality attributes can help to improve the performance parameters of the coffee de-pulping machine and enhance the price of African coffee.
Keywords: Arabica Coffee; Coffee Bean; Coffee Cherry; Coffee Quality; Coffee Processing; De-pulping Process; Robusta Coffee